Tingkat konsumsi zat besi (Fe), seng (Zn) dan status gizi serta hubungannya dengan prestasi belajar anak sekolah dasar - Wadhani, Luh Putu Prema; Yogeswara, Ida Bagus Agung (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : The main problem faced by Indonesia especially in the education field is the achievement of learning in children is still low in Elementary School. Several factor that influence the learning achievement in children are internal factors, external factors and the learning methods. Nutritional status, sufticient iron (Fe) and zinc (Zn) intake is one of the important indicators to improve the growth and development of brain in children.Objective :The purpose of this study to determine the correlation between level of iron and zinc consumption and nutritional status with childrenâ€™ learning achievement in Elementary School no. 1 Buduk and Elementary School no. 2 Abianbase.Methods : design of this study was used an Observational Analytics with Cross Sectional Design which has been implemented in April-May 2017 with Simple Random Sampling Technique in the 5th grade students (57 samples).Result : The result of this study showed that most of the iron (Fe) and zinc (Zn) consumption in medium category that is 64,9% and 42,1%, while the nutritional status in normal category that is 64,9%Â  and the learning achievement includes in good category that is 84,2%. The learning achievement related to iron (Fe) and nutritional status (p=0,000) and not associated with the level of zinc (Zn) consumption (p=0,447).Conclusion : The study showed a correlation between the level of iron (Fe) consumption and nutritional status with learning achievement and there is no correlation between the level of zinc (Zn) consumption.